FRI0428 The Weaker Sex: Characterization of Gender Disparities in A Nationwide Lupus Registry (REUMA.PT LES). (10th June 2014) - Gonçalves, M.J.; Sousa, S.; Inês, L.; Duarte, C.; Borges, J.; Silva, C.; Romão, V.C.; Terroso, G.; Cerqueira, M.; Raposo, A.; Bernardes, M.; Macieira, C.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) is characterized by female predominance with male to female ratio around 1:10. Differences regarding clinical manifestations, disease activity, damage and mortality between men and women with SLE have been reported. Overall it is recognized that gender may affect SLE phenotype, but results concerning disease severity and prognosis are still a matter of debate. Objectives: Characterization of Portuguese SLE male patients, focusing demographic, clinical, and laboratorial features. Methods: All SLE patients from the Portuguese Lupus Register, Reuma.pt/LES were included. Demographic, clinical and therapeutic data were analyzed upon records from the last visit. Student t-tests, chi-square tests and Fisher's exact tests were used to compare male and female patients. Analyses were further adjusted to age and disease duration. Results: Of the 1510 SLE patients registered in Reuma.pt/LES, 122 (8%) are men. Male patients had later onset (39.4±20.6y vs 35.6±14.1y; p=0.005) and shorter disease duration (10.7±7.6y vs 14.1±9.0 y; p=0.0001). Mean current age, racial distribution and education level was similar in the two groups. Serositis, renal involvement and hemolytic anemia were more prevalent in men while, photosensitivity, alopecia, oral ulcers and arthritis were more commonly found in women (Table 1 ). Thyroid disease was more frequent in women (11.4 vs 2.3%). Cardiovascular risk factors had a similar distribution between these groups. Accumulated damage assessed by the SLICC damage index (SDI) and disease activity, assessed by SLEDAI-2K at last visit were similar in the two groups, with adjustment to age and disease duration. Antimalarial drugs and steroids were used more frequently in women. Conclusions: Male patients with SLE are older at disease onset and present a distinct phenotype with less cutaneous, mucous membranes and articular manifestations. However, disease outcome evaluated by the SDI is comparable in men and women, which is in line with observations from other European cohorts. The acknowledgement of the effect of gender on disease manifestations may help physicians in the timely introduction of an appropriate care. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4615